AGAMA DAN KEPRIBADIAN (KAJIAN PENDEKATAN TEKNOLOGI PENDIDIKAN) - Abdul Hadi (Akademika : Jurnal Teknologi Pendidikan, 2018)
Most Ofall Religions Andislam Without Exception, Are Has Theirs Own View On Personality, Either Directly Or Indirectly. This Study Aims To Explain The Religious Values And Personality According To Islamic Point Of View and education technology approach. To Achieve This Goal The Author Take Referrence On Two Main Sources Of Knowledge In Islamic Philosophy, Namely: First, Divine Knowledge (Revelation) The Essence Of Truth Which Is Believed To Right All The Times By The Adherents Of Islam. The Second Is The Paraneal Knowledge (Science) Which Is The Observations Rezult Of Scientists And Philosopy About God, Humans, And The Universe. Implementing for concept and prinsip of values them need to be concreted in order the values of then can be measured by educational tecnology approach. The Approach Used In This Study Is The Qualitative Method With A Library Research Of Islamic Treasures Related To This Title. Religion And Personality Are Like Two Sides Of A Metal Currency Surface Where One And The Other Cannot Be Separated, The Islamic Teachings In Human Behviours Are Believed To Be The Most Important Components In Personality In Order To Accordance With Their Original Nature.